Republic of Poland : Report on Observance of Standards and Codes-Fiscal Transparency Module-Update. (IMF Staff Country Reports; Country Report ;, 2004)
This paper presents an update to the Report on the Observance of Standards and Codes on Fiscal Transparency for Poland. Three state offices were consolidated with the government. Also, the Alimony Fund-an extrabudgetary fund-was liquidated and its functions were shifted to the local governments as of May 1, 2004. The medium-term fiscal reform plan under consideration envisages further consolidation of some extrabudgetary entities and elimination of certain overlapping functions between the central and local governments. Efforts were also made to decentralize fiscal activity and increase the efficiency of public spending.